2023
DOI: 10.1186/s12910-023-00929-6
|View full text |Cite
|
Sign up to set email alerts
|

Should Artificial Intelligence be used to support clinical ethical decision-making? A systematic review of reasons

Lasse Benzinger,
Frank Ursin,
Wolf-Tilo Balke
et al.

Abstract: Background Healthcare providers have to make ethically complex clinical decisions which may be a source of stress. Researchers have recently introduced Artificial Intelligence (AI)-based applications to assist in clinical ethical decision-making. However, the use of such tools is controversial. This review aims to provide a comprehensive overview of the reasons given in the academic literature for and against their use. Methods PubMed, Web of Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…One study delineated that AI has the potential to enhance patient autonomy by enabling patients to receive their treatment of choice. 32 Meanwhile, a research proposed a system that integrated AI estimations, physician's interpretation, and parents’ perspectives to support ethical treatment decisions for newborn patients; The results showed that the system had delivered personalized and customized information to different users and facilitated shared decision-making involving parents. 61 AI can help create adaptive and personalized educational software that can tailor the learning content, pace, feedback, and assessment to each individual learner.…”
Section: Discussionmentioning
confidence: 99%
“…One study delineated that AI has the potential to enhance patient autonomy by enabling patients to receive their treatment of choice. 32 Meanwhile, a research proposed a system that integrated AI estimations, physician's interpretation, and parents’ perspectives to support ethical treatment decisions for newborn patients; The results showed that the system had delivered personalized and customized information to different users and facilitated shared decision-making involving parents. 61 AI can help create adaptive and personalized educational software that can tailor the learning content, pace, feedback, and assessment to each individual learner.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation strategies involve collaborative efforts to align AI with nursing standards, integrate it into existing infrastructure, provide training, and ensure ethical use. These efforts promise to enhance patient care, streamline work ows, and address ethical, legal, and societal concerns, marking a signi cant advancement in nursing practice [38][39][40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…This holistic approach ensures adherence to guidelines and maximizes e ciency and convenience, leveraging the support of family members for an optimal caregiving experience [17]. The deep-learning prediction model and the resultant risk strati cation score may prove helpful in clinical decision-making under time-sensitive and resourceconstrained environments [38][39][40][41][42][43][44][45][46][47].…”
Section: Identify a Model Casementioning
confidence: 99%
“…Ethical Decision Support: Healthcare professionals and contact tracers can make ethical decisions concerning contact tracing and alerts with the support of AI, which offers moral insights and recommendations. When handling sensitive health data, it can help with difficult ethical decisions such as determining the appropriate level of notification and disclosure to individuals who may have been in contact with someone with HIV [51]…”
Section: Ai In Epidemiological Modelingmentioning
confidence: 99%